Community Based Tourism (CBT) Strategy in Developing Kambariat Tuah Pahoe Camping Ground as an Ecotourism Destination in Central Kalimantan - Khusnul Khotimah; Muhammad Farras Nasrida; Puput Iswandyah Raysharie; Benius, Benius (FKIP, Universitas Palangka Raya, 2024)
The study examines the implementation of Community Based Tourism (CBT) strategy in developing Ka mbariat Tuah Pahoe Campsite as an ecotourism destination in Central Kalimantan. Using a mixed-method approach combining quantitative analysis through logistic regression and qualitative descriptive analysis, this research evaluates the effectiveness of community involvement and environmental sustainability in increasing tourist visits. The quantitative findings, supported by a goodness-of-fit test (Hosmer-Lemeshow test p-value: 0.7861) and model accuracy of 91.34%, demonstrate that both community ownership and management (coefficient: 0.413853) and environmental sustainability (coefficient: 0.664741) positively influences visitation rates. Qualitative analysis reveals that the visitor demographic is predominantly young adults aged 18-22 years, indicating potential for youth-oriented tourism development. The study concludes that CBT implementation at Kambariat Tuah Pahoe shows significant promise, particularly when focusing on community empowerment and environmental sustainability, although requiring strategic planning for optimal economic benefit distribution and sustainable environmental management.